Burnout in football coaching - Gáspár, Z.; Szabó, A. (Football Psychology - From Theory to Practice, 2019)
In this chapter we examine the key determinants and consequences of burnout in football coaching. One purpose is to identify the most common causes of stress in coaching whilst reviewing the studies that have examined stress and burnout in this profession. The extant literature is classified so that the internal and external sources of stress, leading to burnout in football coaches, are integrated into an explanatory model for the better understanding of the phenomenon. Another purpose of the review is to identify the key problems in research in the area of sports coaching, with specific focus on football. It is concluded that whilst the majority of research substantiates the stressful nature of the coaching profession, there are numerous inconsistencies in the current literature that need to be addressed through more systematic research. Coaches may perceive their occupation as stressful and their cognitive appraisal of stress is moderated and/or mediated by a variety of personal and situational variables. By exploring available research on the predictors of burnout two groups of factors emerged consisting of intrapersonal (i.e. demographic, dispositional, cognitive) and situational variables. Coaches` longevity in the profession and their psychological and physical health and well-being is at stake if they neglect stress-induced syndromes, such as burnout. Further research is required to identify key determinants of football coaches` burnout. In view of the lack of such research the genuine health risk of football coaching remains speculative.